2010
DOI: 10.1007/s00395-010-0133-0
|View full text |Cite
|
Sign up to set email alerts
|

Remote postconditioning by humoral factors in effluent from ischemic preconditioned rat hearts is mediated via PI3K/Akt-dependent cell-survival signaling at reperfusion

Abstract: Short non-lethal ischemic episodes administered to hearts prior to (ischemic preconditioning, IPC) or directly after (ischemic postconditioning, IPost) ischemic events facilitate myocardial protection. Transferring coronary effluent collected during IPC treatment to un-preconditioned recipient hearts protects from lethal ischemic insults. We propose that coronary IPC effluent contains hydrophobic cytoprotective mediators acting via PI3K/Akt-dependent pro-survival signaling at ischemic reperfusion. Ex vivo rat … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
87
0
6

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(100 citation statements)
references
References 40 publications
7
87
0
6
Order By: Relevance
“…From this point of view, several studies have evaluated the intracellular signalling pathway involved in the cardioprotection afforded by rIPC (Wolfrum et al 2002;Li et al 2010;Breivik et al 2011). However, those authors have not considered the timing sequence of signalling activation.…”
Section: Introductionmentioning
confidence: 99%
“…From this point of view, several studies have evaluated the intracellular signalling pathway involved in the cardioprotection afforded by rIPC (Wolfrum et al 2002;Li et al 2010;Breivik et al 2011). However, those authors have not considered the timing sequence of signalling activation.…”
Section: Introductionmentioning
confidence: 99%
“…insulin improved functional recovery in the older animals, the focal point of this article is to show how variances in outcomes can occur with the same drug with different modes of delivery. It has been shown that coronary effluent from hearts which have undergone prior ischaemic preconditioning contained cytoprotective factors that, when transferred to other hearts, offers protection (9). However to our knowledge our study is novel in that the hearts were not preconditioned, the coronary effluent was used on the same hearts by which it was produced and sanguinarine was the only drug used which caused this effect.…”
Section: Discussionmentioning
confidence: 95%
“…Previous studies demonstrated that some signaling molecules were thought to serve as the upstream mediators of apoptosis during I/R injury [7,9] . The PI3K/Akt pathway is central to physical and pharmacological pre-and post-conditioning and salvaging the ischemia/reperfused myocardium [23][24][25][26] . It has been…”
Section: Discussionmentioning
confidence: 99%